The China-Pakistan economic corridor boosted tourism industry in pakistan and digitalization of society - Ali, Aqib (Bulletin of Social Informatics Theory and Application, 2023)
The China-Pakistan Economic Corridor (CPEC) is a massive undertaking worth more than $ 55 billion, as a result of which the proportionate relationship between Pakistan and China has reached new heights. CPEC should seek to build partnerships between Pakistan and the associations of roads, railway lines, and oil pipelines associated with energy, power, and other systems to ensure a lack of important energy to enhance the advance related to money in Pakistan. CPEC is a lucrative opportunity for Pakistan's moving industry. The CPEC is widely regarded as beneficial to Pakistan's transportation and tourism industries. Through improved structure and transportation, the formation of special currency zones, increased trade movement, and increased trade and trade, the CPEC will alter Pakistan's monetary and trading environment. It relies on individuals from both countries for crucial benefits through the CPEC because it is a tireless attempt with a sane and smooth finish. The main motivation behind this post is to gain knowledge in the advancement of normal appreciation of China's impetus for the revival of the Silk Road, as well as the benefits and challenges for economic movement that the CPEC can bring to border countries, especially Pakistan. An especially original duty will provide us a lot of room to dramatically foster various inventive hotbeds to undermine the idea of organizations and the overall travelers experience in these new traveler places.